Dongeng suka-suka - Ida Silvia 1980; Lail Khair EL Rasyid; Mohammad Hairul; 1983; Nenny Makmun; Nina Rahayu Nadea; Selvy Permatasari Hidayat; 1999; Siti Aminah; 1989; Tommy Alexander Tambunan; 1996; et al. (Leutikaprio, 2012)
Buku ini berisi kumpulan cerita pendek